PENCEGAHAN TKI KEMBALI KE LUAR NEGERI MELALUI PELATIHAN UNTUK DAPAT BERWIRAUSAHA - Dede Rahmat Hidayat (Bahasa Indonesia, 2016)
Indonesia is one of the largest suppliers of informal labor in developed countries in ASEAN, Hongkong, Korea, Japan and Middle East Countries. Unlike the formal workforce that has good protection and income certainty. Workers in the non-formal sector still have vulnerabilities to get problems so there are efforts to reduce and prevent more Indonesians from becoming workers in the informal sector. One strategy is to increase the potential of migrant workers not to go abroad and to prevent ex-migrant workers from returning abroad.How to prevent good is to train the former migrant workers by sharing skills so that they can develop their business independently. The training developed is to train entrepreneurial character and practice business skills. Community service is expected to help the program. Community service activities for former migrant workers are conducted in the form of entrepreneurship training. In this activity the participants are former TKI in Sukabumi which amounted to 20 people, conducted in Cibolang Village Gunung Guruh District.